Experimental and Numerical Studies on the Mechanical Properties of Columnar Jointed Basalt - Shiyi Zhu; Changdi He; Fei Peng; Anchi Shi; Dongyang Yuan; Weikang Zhang (Advances in Civil Engineering)
Columnar jointed basalts (CJB) are featured by the joint network of discontinuities, which is hard for geotechnical design and construction. Therefore, investigating the mechanical behaviors of CJB is significant for the long-term use of the engineering structures. In this paper, field research studies, such as the rigid bearing plate tests and acoustic tests, were employed, to obtain the deformation modulus and the acoustic velocity of columnar jointed basalts, and the formula expressed by deformation modulus and acoustic velocity was then established, which would be a useful guidance for the site operation. Based on the monitoring and testing data of CJB, several numerical simulation models with different joint angles and weak thickness were built to further discuss the mechanical behaviors of CJB. The numerical simulation results show that the joint angle of 30° ∼ 60° presents weak antipressure abilities, for the shearing slipping force and interformational sliding are remarkable in them. Besides, the small material property difference is helpful for the compressive strength of rock masses. After adopting the most unfavorable joint angle and width to model the tunneling process in CJB, it suggests that it is easily damaged along the directions of rock joints in CJB when constructing in tunnels.